A Reconfigurable Coplanar Waveguide Bowtie Antenna Using an Integrated Ferroelectric Thin-Film Varactor. (17th July 2012) - Pan, K. C.; Brown, D.; Subramanyam, G.; Penno, R.; Jiang, H.; Zhang, C. H.; Patterson, M.; Kuhl, D.; Leedy, K.; Cerny, C.
Abstract : A novel printed antenna with a frequency reconfigurable feed network is presented. The antenna consists of a bowtie structure patch radiating element in the inner space of an annulus that is on a nongrounded substrate with a ferroelectric (FE) Barium Strontium Titanate (BST) thin film. The bowtie patch is fed by a coplanar waveguide (CPW) transmission line that also includes a CPW-based BST shunt varactor. Reconfiguration of the compact 8 mm × 8 mm system has been demonstrated by shifting the antenna system's operating frequency 500 MHz in the 7–9 GHz band by applying a DC voltage bias.